Assessing Student Satisfaction with the Korean Language Program at Sejong Korean Academy of Yogyakarta - Izzulhaq, Muhammad Haikal; Darmanto, Darmanto; Fitra Jasmine Adefiannisa (Sean Institute, 2025)
This study aims to analyze the student satisfaction of Sejong Korean Academy of Yogyakarta with the EPS-TOPIK Korean language program. This study used a qualitative descriptive method by using questionnaires to obtain research data. Based on the research results, it was found that four indicators of consumer satisfaction, namely, service quality, price, situational factors and personal factors have a positive influence on student satisfaction. Quality of service includes experienced instructors, interactive learning methods, learning materials and adequate learning resources. Affordable price factors match the quality that students expect. Situation factors include flexible learning schedules and strategic institutional locations. Personal factors indicate that the recommendation of relatives or family members is the dominant factor for students’ satisfaction. The study showed that these four indicators of consumer satisfaction affect students’ satisfaction with the Korean language programs they participate in.